Organizational Commitment Model - Mauli Siregar, Rianda; Erwansyah; B, Mesra (International Conference Epicentrum of Economic Global Framework, 2026)
This study aims to analyze the influence of the work environment and organizational culture on organizational commitment, with job stress serving as a mediating variable at the BPJS Employment Regional Office of Northern Sumatra. The study was motivated by the relatively low level of organizational commitment indicated by the pre-survey results, as well as less-than-optimal work environment and organizational culture conditions accompanied by high levels of employee job stress. This research employed a quantitative approach with an associative research design. The study population consisted of 75 employees from the BPJS Employment Regional Office of Northern Sumatra, BPJS Employment Medan Utara Branch Office, and BPJS Employment Binjai Branch Office. A saturated sampling technique was applied, whereby all members of the population were included as research respondents. Data were collected through questionnaires and analyzed using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method with SmartPLS software. The results indicate that organizational culture has a positive and significant effect on organizational commitment and a negative and significant effect on job stress. The work environment has a negative and significant effect on job stress but does not have a significant direct effect on organizational commitment. Furthermore, job stress has a negative and significant effect on organizational commitment. The indirect effect analysis demonstrates that job stress significantly mediates the relationship between organizational culture and organizational commitment, as well as the relationship between the work environment and organizational commitment. These findings suggest that improving organizational commitment depends not only on fostering a strong organizational culture and a supportive work environment but also on the organization’s ability to effectively manage employees’ job stress.